Chirality‐Dependent Magnetoelectric Responses in a Magnetic‐Field‐Induced Ferroelectric Phase of Pb(TiO)Cu4(PO4)4. (28th April 2022) - Kimura, Kenta; Katsuyoshi, Tsukasa; Miyake, Atsushi; Tokunaga, Masashi; Kimura, Shojiro; Kimura, Tsuyoshi
Abstract: Magnetoelectric multiferroic materials can exhibit a variety of functional properties such as electric field control of magnetization and nonreciprocal electromagnetic responses. Such a magnetoelectric response may be further enriched by the combination of the magnetoelectric order and a peculiar crystallographic order, such as crystal chirality. Recently, it was reported that a chiral‐lattice magnet Pb(TiO)Cu4 (PO4 )4 showing a magnetoelectric quadrupole order in its ground state exhibits anomalous chirality‐induced tilt of magnetization vector with respect to an applied magnetic field. In this progress report, additional results that advance the understanding of chirality‐induced tilt of magnetization vector are presented. It is found that chirality‐induced tilt of the magnetization vector also exists in a magnetic‐field‐induced ferroelectric (FI‐FE) phase of this compound that is stabilized in magnetic fields higher than 16 tesla. The resulting transverse component of the magnetization can be switched with an applied electric field through a polarization reversal. The analysis indicates that this transverse component is as large as ≈0.014 μB per f.u, suggesting that the tilting angle of the magnetization in the FI‐FE phase is much larger than that in the low‐field phase. Also, as another research progress, electric field control of nonreciprocal directional dichroism in the FI‐FE phase is demonstrated. Abstract : In a magnetic‐field‐induced multiferroic phase of a chiral‐lattice magnet Pb(TiO)Cu4 (PO4 )4, it is found that the crystal chirality tilts the magnetization vector from the applied magnetic field direction and its tilted component is switchable with an applied electric field. It is proposed that the tilted magnetization can generally exist in chiral‐lattice multiferroics with crossed electric polarization and magnetization.